The Use of PELOD Score in Predicting Acute Kidney Injury in Critically Ill Children - Prasetyo, Risky Vitria; Saraswati, Putu Dian; Kurniawan, Muhammad Riza; Kushartono, Hari; Soemyarso, Ninik Asmaningsih; Azis, Abdul Latief; Noer, Mohammad Sjaifullah (Journal of Nepal Paediatric Society, 2016)
Introduction: Acute kidney injury (AKI) significantly increases morbidity and mortality in critically ill children. Prognostic indicators such as Pediatric Logistic Organ Dysfunction (PELOD) score is associated with factors related to renal dysfunction. The aim of this study was to study the AKI incidence and correlate the PELOD score with AKI in critically ill children admitted to PICU at Dr. Soetomo Hospital Surabaya Indonesia. Material and Methods: A prospective study was conducted to all children admitted to PICU during 15 January-14 April 2014. Demographic data (age, sex, PICU indications, PELOD scores, AKI staging by pRIFLE at admission) and outcome after 7 days at PICU were recorded. All data were analyzed descriptively (p<0.05). Results: A total of 56 (47.1%) out of 119 children were studied. The rest was excluded for being <3 months old, had end-stage kidney disease or complex cardiac problem, and cardiac catheterization. Mean age of subjects was 49.7 (SD 46.2) months, male-to-female ratio of 1.2:1. PICU indication was dominated by shock (35.7%), followed by CNS dysfunction in 13 (23.2%) and respiratory failure in 12 (21.4%) children. AKI was noted in 15 (26.8%) children, mostly (10.7%) in Injury stage with 5 (8.9%) in Risk and 4 (7.1%) in Failure stages. PELOD scores at admission ranged from 0 to 20 (mean 4.34, SD 5.87), higher scores in AKI group (7.8±6.64 vs 3.1±5.09, P=0.013). Twelve (21.4%) children died, 7 (58.3%) had AKI with 3 (25.0%) each in Risk and Failure while 1(8.3%) in Injury (p<0.05). Conclusion: PELOD score can be used as a predictor for AKI in critically ill children. J Nepal Paediatr Soc 2016;36(2):165-169.